The expression of the nth term can be written using the formulas
A. nth term =
![4 + (n-1)(-3)](https://img.qammunity.org/2022/formulas/mathematics/high-school/r7lio1s35vsbl12yvi2lvqfa1zvqxzp1li.png)
B. nth term =
.
The expression of the nth term can be written as:
For the sequence 4, 1, -2, -5, -8............................
the first term a = 4 and the common difference d = -3.
aₙ =
![a + (n-1) d](https://img.qammunity.org/2022/formulas/mathematics/high-school/rakwm919irgqewtm7bz0z9nwhp5s8s3qzs.png)
aₙ =
![4 + (n-1)(-3)](https://img.qammunity.org/2022/formulas/mathematics/high-school/r7lio1s35vsbl12yvi2lvqfa1zvqxzp1li.png)
Therefore, the nth term is given by the formula aₙ =
.
For the sequence -7, -12, -17, -22, -27...................
the first term a = 7 and the common difference d = -5.
aₙ =
![a + (n-1) d](https://img.qammunity.org/2022/formulas/mathematics/high-school/rakwm919irgqewtm7bz0z9nwhp5s8s3qzs.png)
aₙ =
![-7 + (n-1)(-5)](https://img.qammunity.org/2022/formulas/mathematics/high-school/6ai1ky6i6pl81ts1oqb9zg7ipffxgx8ndf.png)
Therefore, the nth term is given by the formula aₙ =
.